Edwin Morgan and Russian Poetry. (2nd January 2020) - France, Peter
ABSTRACT: Edwin Morgan (1920–2010), first poet laureate (makar) of Scotland, was a prolific translator of poetry from about twenty European languages into both Scots and English. Translations from Russian bulk large in his Collected Translations (1996). The most famous of these is Wi the Haill Voice, his vigorous and inventive transposition of Mayakovsky into Scots. This work is examined here, alongside Morgan's always faithful translations from Pushkin and from two very different younger contemporaries, Voznesensky and Aygi.